Modeling Arterial Blood Flow under Stenosis: A Comparative Study of Newtonian and Carreau-Yasuda Non-Newtonian Approaches - Erwin; Marpaung, Jonathan Liviera (Talenta Publisher, 2024)
This study investigates the simulation of blood flow within arteries experiencing stenosis using both Newtonian and non-Newtonian models. The Newtonian model employs standard fluid dynamics assumptions, while the non-Newtonian Carreau-Yasuda model accounts for the unique viscoelastic properties of blood, providing a more accurate representation of its flow behavior under various shear rates. By utilizing COMSOL Multiphysics, the simulations are conducted with parameters including blood velocity, viscosity, and pressure in normal and narrowed artery conditions. Results reveal that while the Newtonian model predicts general flow patterns, it lacks the precision needed to reflect the complexities of blood behavior in stenosed regions. Conversely, the Carreau-Yasuda model demonstrates enhanced accuracy by capturing viscosity variations and pressure differentials, particularly in the narrowed artery sections, showing the significance of non-Newtonian characteristics in modeling blood flow. These findings underscore the potential of non-Newtonian models in improving diagnostic and therapeutic approaches for vascular conditions.